Welfare Level of Fishermen’s Household Around the Mangrove Ecosystem in Khairiah Mandah Village - Mandela, Hades; Fahrudin, Achmad; Yulianto, Gatot (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
The majority of fishermen are the small-scale group who are depending on marine resources which utilization results are unsettled so that this group vulnerable to a low welfare state. On the other hand, the abundant marine resources in the mangrove ecosystem have not been able to be managed optimally to improve the welfare of fishermen's household. Therefore, the purpose of this study is to measure the welfare state of fishermen's household around the mangrove ecosystem. This research was conducted in the Khairiah Mandah Village from December 2019 to January 2020 using a survey method. The technique was determining respondents using purposive sampling with 39 fishermen consisting of 13 fishermen who catch fish, 13 fishermen who catch shrimp, and 13 fishermen who catch crabs. Data analysis uses analysis of the level of family welfare with indicators of a prosperous family according to BKKBN. The results showed that the fishermen around the mangrove ecosystem were mostly in the Prosperous Family I group with a percentage of 56%. Besides, fishermen families who are in the Prosperous Family II group are 31%, Prosperous Family III is 8%, Pre-Prosperous Family is 5%, and none are included in the Prosperous Family III Plus group.